Environmental Conservation Policy Model Based on the Protection of Indigenous Peoples in Indonesia - Pangestu, Ilham Aji; Latif, Inas Sofia; Nuralifa, Chika Putri; Pratama, Rommy (SASI, 2023)
Introduction: Indigenous peoples are an order of society that existed even before the Indonesian nation was born. The Indonesian state recognizes the existence of indigenous peoples and their rights. The legal protection of indigenous peoples is the responsibility of the state as mandated by the constitution and other relevant laws and regulations regarding the management of natural resources. However, there are still conflicts between indigenous peoples, the government, and companies that have received management permits from the government.Purposes of the Research: This study aims to review and provide a policy model formulation regarding the protection of indigenous peoples in the context of environmental conservation.Methods of the Research: Researchers use normative legal research methods that examine through a statutory approach and a case approach. Legal materials are obtained through literature studies, both primary and secondary legal materials that are relevant to the problem under study.Results of the Research: The results show that currently the arrangements that are a form of recognition and protection of indigenous peoples are still scattered in many laws and regulations. Even though it has been regulated, the arrangement is still not enough, so a policy model for the protection of indigenous peoples is needed that also firmly provides protection in the context of preserving the environment. Because in fact indigenous peoples and the environment are an inseparable part.